Retina mirrors brain pathology and response to GA immunotherapy in advanced stage AD‐model mice. (December 2021) - Doustar, Jonah; Rentsendorj, Altan; Torbati, Tania; Regis, Giovanna C.; Fuchs, Dieu‐Trang; Sheyn, Julia; Mirzaei, Nazanin; Graham, Stuart; Shah, Prediman K; Mastali, Mitra; Eyk, Jennifer E; Black, Keith L; et al.
Abstract: Background: Characteristic signs of Alzheimer's disease (AD) are increasingly reported in the neurosensory retina of human patients and animal models, however examination of the retino‐cerebral relationship, especially at late disease stages and in response to therapy, is scarce. Transgenic models of AD (APPSWE /PS1∆E9 ; ADtg mice) treated with glatiramer acetate (GA) immunomodulation showed disease alleviation in pre‐ and early‐symptomatic disease stages. Here, we explored the link between retinal and cerebral AD‐related biomarkers, including response to GA immunization, in cohorts of old, advanced‐stage ADtg mice. These mice were aged to become more clinically relevant to AD. Method: To determine the extent of amyloid β‐protein (Aβ) burden in retinal and brain tissues from treated and untreated ADtg mice, we developed a new protocol for extracting, unfolding and quantifying Aβ levels utilizing a Meso Scale Discovery biochemical assay, which recognizes human and mouse Aβ1‐42, Aβ1‐40, and Aβ1‐38 proteins. Homogenates from these tissues were additionally analyzed by mass spectrometry for detailed global protein levels. Immunohistochemical staining for Aβ plaques, inflammation, infiltrating myeloid cells, and synapses were conducted on brain sections to reveal cerebral effects of GA immunotherapy. Result: Levels of synaptotoxic Aβ1‐42, angiopathic Aβ1‐40, non‐amyloidogenic Aβ1‐38, and Aβ42 /Aβ40 ratios tightly correlated between paired retinas derived from oculus sinister (OS) and oculus dexter (OD) eyes, and between left and right brain hemispheres. Brains and retinas displayed significant, one‐side dominant lateralization of Aβ burden. Importantly, OS and OD retinal Aβ levels correlated with their cerebral counterparts, in advanced disease stage and following GA immunotherapy, with stronger contralateral correlations. Moreover, immunomodulation in old ADtg mice provoked reductions in vascular and parenchymal Aβ deposits in the brain, especially of large, dense‐core plaque subtypes, and alleviation of microgliosis and astrocytosis. Immunization further enhanced cerebral recruitment of peripheral myeloid cells and synaptic preservation. Global proteome profiling by mass spectrometry revealed novel molecular parallels in retino‐cerebral AD‐related pathology and response to GA immunization, including restoration of homeostatic astrocytic glutamine synthetase expression. Conclusion: Overall, our results support the sustainability of immunomodulation in provoking CNS repair, even in advanced‐stage AD‐model mice, while revealing similarities in retino‐cerebral responses to therapy, providing incentives to explore retinal AD biomarkers.